Clinical benefit and risk of elemene in cancer patients undergoing chemotherapy: a systematic review and meta-analysis - Pan, Yanhong; Wan, Panting; Zhang, Li; Wang, Cuirong; Wang, Yijun (Frontiers in Pharmacology, 2023)
Elemene injection and oral emulsion, known as elemene, have been utilized have been used in adjuvant therapy for cancer patients in China for more than 20 years. In order to evaluate the efficacy and potential risks of the treatments in cancer patients undergoing chemotherapy, a comprehensive search was conducted across various databases including PubMed, Cochrane Library, Web of Science, EMBASE, CKNI, Wan Fang, and VIP databases. Additionally, the factors that may influence the outcomes were also explored. Meta-regression, subgroup, and sensitivity analyses were conducted to explore the heterogeneity. GRADE system and TSA were used to assess the strength of evidence and robustness of the results. The pooled data showed that combination with elemene could improve the response rate (RR:1.48, 95%CI:1.38-1.60, P<0.00001), disease control rate (RR:1.20, 95%CI:1.15-1.25, P<0.00001), the rate of quality-of-life improvement and stability (WMD:1.31, 95% CI:1.12-1.53, P=0.0006), immune function (CD4+/CD8+: WMD:0.33, 95% CI:0.24-0.42, P<0.00001), survival rate (1-year, RR:1.34, 95% CI:1.15-1.56, P=0.0002; 2-year, RR:1.57, 95% CI:1.14-2.16, P=0.006), and decrease the prevalence of most chemotherapy-induced side effects, especially leukopenia (Ⅲ-Ⅳ) (RR:0.46, 95% CI:0.35-0.61, P<0.00001), thrombocytopenia (RR:0.86, 95% CI:0.78-0.95, P=0.003), and hemoglobin reduction (RR:0.83, 95% CI:0.73-0.95, P=0.007). However, the administration of elemene has been found to significantly increase the incidence of phlebitis in patients undergoing chemotherapy (RR:3.41, 95% CI:1.47-7.93, P=0.004). Meta-regression and subgroup analyses discovered that the outcomes were rarely influenced by CR, CT, and dosage of elemene (DE) but the cycle number of elemene (CNE) and TT were the main sources of heterogeneity. As the treatment time and the number of cycles increased, the efficacy of the elemene combination decreased across various aspects. Thus, shorter duration and fewer cycles are recommended.